If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ln(3 + -2x) = 11 (3 * ln + -2x * ln) = 11 (3ln + -2lnx) = 11 Solving 3ln + -2lnx = 11 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Reorder the terms: -11 + 3ln + -2lnx = 11 + -11 Combine like terms: 11 + -11 = 0 -11 + 3ln + -2lnx = 0 The solution to this equation could not be determined.
| 7x^3+14x^2= | | 8-a=24 | | x+9.3=32.7 | | x+9.3=31.7 | | a-12=-4 | | 8x^2+59x=-21 | | 128x^6=0 | | 3.9x+2.1=13.8 | | 36x-72=9 | | 7x+35=42 | | 7x+35=41 | | F(x)=(3x+3)(-2x+6) | | Fx=2x^2+4x+2 | | 0.5=a(3.5)2+b(3.5) | | Fx=2x^2+12x+17 | | 0.5=a(3.5)+b | | 16x^2-48x+3=35 | | 16x-64=16 | | 18000=(24x)+(x-100) | | 2p=145 | | 09x-13=-103 | | 18500=(24x)+(x-100) | | g(x+3)=3x-4 | | y=4.21(7) | | X^2-100x-770=0 | | y=4.21x | | f(x+3)=3x^2-2x-4 | | 10x+12=72.00 | | 40x+15x=960 | | c-5+1.00=9.00 | | (5X-2)=2X+4 | | 2k-4=k+9 |